2016
DOI: 10.1002/ajp.22618
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional ecology of wild Bornean orangutans (Pongo pygmaeus wurmbii) in a peat swamp habitat: Effects of age, sex, and season

Abstract: The spatial and temporal variation in food abundance has strong effects on wildlife feeding and nutrition. Here we present the first long term study of the effects of variation in fruit availability and age/sex class on nutritional ecology of wild Bornean orangutans. We examined variation in nutrient intake of wild orangutans in living in a peat swamp habitat over a 7-year period at the Tuanan Orangutan Research Station in Central Kalimantan. We conducted 2,316 full-day focal follows on 62 habituated orangutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
65
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 87 publications
4
65
1
Order By: Relevance
“…( 22 , 51 )]. Top: The percentage of fruiting trees derives from 1868 marked trees in monthly monitored phenology plots, 98% of which are species consumed by orangutans.…”
Section: Discussionmentioning
confidence: 99%
“…( 22 , 51 )]. Top: The percentage of fruiting trees derives from 1868 marked trees in monthly monitored phenology plots, 98% of which are species consumed by orangutans.…”
Section: Discussionmentioning
confidence: 99%
“…Seasonal changes in food availability also relate to diet selection, driving variation in food item types, and sometimes nutrients consumed. For example, energy intake in orangutans ( Pongo pygmaeus wurmbii ) related positively to seasonal fruit availability (Vogel et al, ). Sifakas ( Propithecus verreauxi ) consumed more total nonstructural carbohydrates (TNC), structural carbohydrates (neutral detergent fiber (NDF)), fat and overall energy during the late wet season compared with early wet and dry seasons (Koch, Ganzhorn, Rothman, Chapman, & Fichtel, ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, there were virtually no significant differences in the relative contributions of different macronutrients to ME among seasons. Thus, C. a. palliatus at Diani were able to maintain consistent relative macronutrient intakes across seasons, unlike some other primate species who face more drastic seasonal changes in food availability and must alter their macronutrient intakes (Conklin‐Brittain et al, ; Irwin et al, , ; Koch et al, ; Vogel et al, ).…”
Section: Discussionmentioning
confidence: 95%
“…Some caution should be exercised when comparing the results of this study to other GF nutritional ecology studies due to the differences in methods and statistical approaches. While many previous studies have reported daily nutrient intakes based on full‐day follows of individuals (Felton, Felton, Raubenheimer, et al, 2009; Felton, Felton, Wood, et al, 2009; Irwin et al, ; Johnson et al, ; Rothman et al, ; Vogel et al, ), this study combined behavioral scans used to estimate time spent feeding on various species‐specific plant parts with short focal follows used to quantify ingestion rates of species‐specific plant parts. Rather than reporting true daily nutrient intake estimates, this study estimated an individual's nutrient intake over the course of a monthly observational period and divided these values by the number of days an individual was observed (i.e., to scale data to daily intake values).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation